Barriers and enablers to adolescent self-consent for vaccination: A mixed-methods evidence synthesis. Issue 3 (14th January 2019) - Fisher, Harriet; Harding, Sarah; Hickman, Matthew; Macleod, John; Audrey, Suzanne
Highlights: Synthesis of studies related to self-consent procedures for adolescent vaccination. Robust systematic review methodology used to identify and appraise the literature. There is a need to clarify policy and address professionals' misunderstandings. Concerns about professional practice and relationships with parents create barriers. Enabling adolescent self-consent entails disputing the primacy of parental consent. Abstract: Introduction: The recent global expansion of routine adolescent vaccination programmes has the potential to protect young people against infectious diseases and improve their health. Although the legal framework in many countries permits young people to consent for vaccinations if competent, lack of written parental consent can still prevent uptake. We aimed to review systematically the associated barriers and enablers to implementation of adolescent self-consent procedures. Methods: A comprehensive search strategy of ten databases from inception to June 2018 was undertaken to identify relevant qualitative and quantitative studies. Titles, abstracts and full texts were assessed for eligibility, and the methodological quality of eligible primary studies evaluated. Thematic synthesis methods were used to interpret and combine qualitative data, and to identify overarching themes as well as similarities and differences within themes. Quantitative data were summarised and, because the data were sufficiently similar in focus, were integrated within the qualitative framework. Results: Twenty-five publications related to 23 studies were included. Three themes were identified which related to the policy framework, protection, and self-determination. Despite supportive national policy frameworks, implementation of adolescent self-consent procedures can be prevented by local policies, professionals' misunderstandings of the legal framework and the context in which the vaccination programme is delivered. Motivation to protect young people's health increased acceptability of adolescent self-consent, but implementation might be prevented to protect the reputation of professionals or relationships with parents. Further, maintaining the role of parents as decision-makers for their child's healthcare was frequently prioritised over enabling young people's autonomy to consent. Conclusions: Barriers to the implementation of adolescent self-consent procedures have implications for young people's health and uptake of vaccination programmes. There is a need to clarify the policy framework and challenge the primacy of parental consent. Systematic review registration: PROSPERO CRD42017084509.